Not coming in today - firm productivity differentials and the epidemiology of the flu - Matthias Dorner; Peter Haller (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
With more than four million cases in Germany every year, influenza and acute upper respiratory tract infectious diseases (henceforth URTI) exhibit the highest number of reported doctor consultations. Although the direct treatment costs for URTI are comparably low, the indirect economic costs, due to work absences and productivity impairments of sick workers who remain at work (presentism), are far more compelling. In this paper, we estimate the effect of local URTI incidences as an exogenous shock to the production factor labor and thus on firm productivity. To quantify the URTI related shock on the production factor labor, we scrape a large number of weekly maps depicting the (local) URTI index across Germany, which are provided in the official influenza surveillance system. Measured by the length of the influenza season in German municipalities from 2003 to 2009, these data exhibit substantial seasonal as well as regional variation. In our main analysis, we estimate firm level production functions using data from the IAB Establishment Panel, a comprehensive German firm survey. In our main regression, we analyze total factor productivity differentials and their relationship with the local influenza intensity. We find sizeable negative effects of the URTI diseases on firm productivity. We attribute this effect to a combination of direct productivity losses caused by absences of sickworkers as well as indirect productivity impairments due to presenteeism. – – Mit mehr als vier Millionen Fällen pro Jahr in Deutschland nehmen Influenza und akute Infektionskrankheiten der oberen Atemwege (URTI) die Spitzenposition unter den gemeldeten Arztbesuchen in Deutschland ein. Obwohl die direkten Behandlungskosten vergleichsweise niedrig sind, sind die indirekten wirtschaftlichen Kosten aufgrund von Fehlzeiten und Produktivitätseinbußen bei kranken Arbeitnehmern, die am Arbeitsplatz verbleiben (Präsentismus), weitaus bedeutsamer. In diesem Papier schätzen wir den Einfluss lokaler URTI-Inzidenz als exogenen Schock für den Produktionsfaktor Arbeit und damit für die Produktivität von Firmen. Um den Schock auf den Produktionsfaktor Arbeit zu quantifizieren, extrahieren wir aus einer großen Zahl an Karten aus dem offiziellen Grippe-Überwachungssystem den lokalen URTI-Index. Bezogen auf die Dauer der Grippesaison in deutschen Gemeinden von 2003 bis 2009 zeigen unsere Daten erhebliche saisonale und regionale Schwankungen. In unserer Analyse schätzen wir Produktionsfunktionen auf Unternehmensebene anhand von Daten aus dem IAB-Betriebspanel. In unserer Hauptregression analysieren wir Produktivitätsunterschiede und deren Zusammenhang mit der lokalen URTI-Intensität in einem Jahr. Wir finden negative Auswirkungen von URTI auf die Produktivität von Unternehmen. Wir führen diesen Effekt auf eine Kombination aus direkten Produktivitätsverlusten durch Fehlzeiten kranker Mitarbeiter sowie indirekten Produktivitätseinbußen durch Präsentismus zurück.
Keywords: L25; I12; J24; R1; 330; flu; productivity; regional